177k views
1 vote
The answer could be A or c but idk which one is the right one please help

The answer could be A or c but idk which one is the right one please help-example-1
User Ryudice
by
6.3k points

2 Answers

1 vote
The answer would be c


User Zernel
by
5.8k points
2 votes
2x2 -2x - 9 = 0
For this case, what we should do is use the resolver.
We have then:
x = (- b +/- root (b ^ -4ac)) / 2a
a = 2
b = -2
c = -9
Substituting the values:
x = (- (- 2) +/- root ((- 2) ^ - 4 (2) (- 9))) / 2 (2)
Rewriting:
x = (2 +/- root (4 + 72)) / 4
x = (2 +/- root (76)) / 4
x = (2 +/- root (19 * 4)) / 4
x = (2 +/- 2raiz (19)) / 4
x = (1 +/- root (19)) / 2
Answer:
option C
x = (1 +/- root (19)) / 2
User Beyeran
by
5.8k points